(untitled) (Research, Society and Development, 2025)
Mass movements affecting unstable slopes largely result from the influence of external factors, such as the infiltration of rainwater, improper disposal of surface water, cuts executed without technical criteria, and the application of overloads from buildings. To mitigate these effects and increase the safety of areas, different retaining systems can be employed, varying in materials used, performance, and construction cost. Among the available alternatives, the use of geosynthetics has gained prominence. These polymeric materials, industrially manufactured, are applied with the aim of improving or replacing conventional solutions in geotechnical works. Their advantages include increased tensile resistance of the soil mass, ease of installation, low cost, and rapid execution. In this context, the present study proposes the adoption of a reinforced-soil solution using geogrids to stabilize the slope located at Km 19 of BR-230, in João Pessoa, an area marked by recurrent landslides during periods of high rainfall. The preliminary design was carried out considering internal and external stability checks, with the Safety Factor evaluated using the GeoSlope software, which indicated a significant increase in resistance. Based on the proposed solution, a preliminary cost estimate was prepared and compared with alternatives previously studied for the same location. The costs of the anchored retaining wall were updated according to DNIT adjustment indices. The results demonstrated that the geogrid-reinforced soil presents lower costs, establishing itself as a technically efficient and economically viable alternative.